The benefits of 3D laser scanning - Kushnir, D. V. (ТДАТУ, 2021)
Although the first scanning systems are relatively recent, laser scanning technology has proven to be highly effective and is actively replacing less productive measurement methods.
Keywords: geodesy; 3D laser; terrestrial 3D laser scanning